xUBF and Rib 1 are both required for formation of a stable polymerase I promoter complex in X. laevis. - McStay, B (1991)
We show that three protein fractions are required for accurate transcription initiation at a Xenopus laevis ribosomal gene promoter in vitro: RNA polymerase I, Rib1 and xUBF. The Rib1 and xUBF fractions are both necessary and sufficient for formation of a stable initiation complex. The xUBF fraction can be completely replaced by recombinant xUBF. We also report the sequence of a cDNA clone for xUBF. xUBF is 701 amino acids in length, contains domain which are related to a domain found in chromosomal proteins HMG 1 and 2, and has an acidic carboxy terminus of 87 amino acids. xUBF is closely similar in amino acid sequence to its previously reported human homolog, hUBF, except that xUBF has only three of the HMG-related domains while hUBF has four and therefore is 63 amino acids longer than xUBF.